RNA-Seq Analyses Identify Frequent Allele Specific Expression and No Evidence of Genomic Imprinting in Specific Embryonic Tissues of Chicken - Zhuo, Zhu (Sci Rep, 2017)
Epigenetic and genetic cis-regulatory elements in diploid organisms may cause allele specific expression (ASE) – unequal expression of the two chromosomal gene copies. Genomic imprinting is an intriguing type of ASE in which some genes are expressed monoallelically from either the paternal allele or maternal allele as a result of epigenetic modifications. Imprinted genes have been identified in several animal species and are frequently associated with embryonic development and growth. Whether genomic imprinting exists in chickens remains debatable, as previous studies have reported conflicting evidence. Albeit no genomic imprinting has been reported in the chicken embryo as a whole, we interrogated the existence or absence of genomic imprinting in the 12-day-old chicken embryonic brain and liver by examining ASE in F1 reciprocal crosses of two highly inbred chicken lines (Fayoumi and Leghorn). We identified 5197 and 4638 ASE SNPs, corresponding to 18.3% and 17.3% of the genes with a detectable expression in the embryonic brain and liver, respectively. There was no evidence detected of genomic imprinting in 12-day-old embryonic brain and liver. While ruling out the possibility of imprinted Z-chromosome inactivation, our results indicated that Z-linked gene expression is partially compensated between sexes in chickens.